2021
DOI: 10.1097/ccm.0000000000005334
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Blocker Use in Critically Ill Children: Assessing Mortality Risk by Propensity Score–Weighted Analysis

Abstract: We aim to describe the use of continuous infusion of neuromuscular blocking agents in mechanically ventilated critically ill children and to test its association with in-hospital mortality.DESIGN: Multicenter, registry-based, observational, two-cohort-comparison retrospective study using prospectively collected data from a web-based national registry. SETTING:Seventeen PICUs in Italy. PATIENTS:We included children less than 18 years who received mechanical ventilation and a neuromuscular blocking agent infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, the adverse consequences of these drugs cannot be ignored and children on ECMO are at risk of these consequences. 9,19 We observed that nearly half of the respondents have and follow a protocolized sedation strategy. Although there has been no conclusive evidence on the utility of protocolized sedation in critically ill children, it is being followed with the assumption that having and adhering to a protocol may improve the outcomes in critically ill children.…”
Section: Discussionmentioning
confidence: 93%
“…However, the adverse consequences of these drugs cannot be ignored and children on ECMO are at risk of these consequences. 9,19 We observed that nearly half of the respondents have and follow a protocolized sedation strategy. Although there has been no conclusive evidence on the utility of protocolized sedation in critically ill children, it is being followed with the assumption that having and adhering to a protocol may improve the outcomes in critically ill children.…”
Section: Discussionmentioning
confidence: 93%